Chylothorax due to left brachiocephalic vein thrombosis as a late complication of pacemaker implantation - Tomaszewski, Dariusz; Marjański, Tomasz; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Pacemaker implantation resulting in lymph leakage to the pleural cavity is exceptionally rarely reported in the medical literature. We report a case of a 87-year-old patient who developed left brachiocephalic vein thrombosis on pacemaker electrodes 12 years after implantation. Due to lack of flow from the thoracic duct to the left venous angle, the thoracic duct cracked and lymph leaked to the right pleural cavity. Supradiaphragmatic ligation of the thoracic duct in right thoracotomy efficiently ceased lymph leakage.